Heat transfer enhancement for corrugated facing step channels using aluminium nitride nanofluid - numerical investigation - Azeez, Kafel; Abu Talib, Abd Rahim; Ahmed, Riyadh Ibraheem (Yildiz Technical University, 2022)
The present work carries out a three-dimensional numerical analysis study of Aluminium Nitride (AlN)-water hybrid nanofluid enhanced heat transfer in laminar forced convection flow heat exchanger with four different channels, flat, backward facing step, triangle and trapezoidal facing step channels. The influence of different Reynolds number (100≤ Re ≤1500) and different solid nanoparticles volume fraction (1% and 4%) on the heat transfer and fluid flow were numerically investigated. The numerical analysis was carried out by using a laminar model of ANSYS-Fluent CFD code and the governing equations were resolved using the finite volume method. The results indicate that the thermal conductivity of the nanofluids increases with the increase values of both the nanoparticles volume fractions and Reynolds number, compared with base fluids. Likewise, the pressure drop showed slightly increased due to the increased of both parameters. The use of high nanoparticles volume fractions (4% volume) nanofluid corresponded with the use of four different channel designs resulted in heat transfer augmentation about 30% when compared to that pure water for the trapezoidal channel.